Dexterous Manipulation During Rhythmic Arm Movements in Mars, Moon, and Micro-Gravity - Opsomer, Laurent; Théate, Vincent; Lefèvre, Philippe; Thonnard, Jean-Louis (Frontiers in Physiology, 2018)
Predicting the consequences of one’s own movements can be challenging when confronted with completely novel environmental dynamics, such as microgravity in space. The absence of gravitational force disrupts internal models of the central nervous system (CNS) that have been tuned to the dynamics of a constant 1-g environment since birth. In the context of object manipulation, inadequate internal models produce prediction uncertainty evidenced by increases in the grip force (GF) safety margin that ensures a stable grip during unpredicted load perturbations. This margin decreases with practice in a novel environment. However, it is not clear how the CNS might react to a reduced, but non-zero, gravitational field, and if adaptation to reduced gravity might be beneficial for subsequent microgravity exposure. That is, we wondered if there may be a transfer of learning from one reduced gravity field to another. In this study, we investigated the kinematics and dynamics of vertical arm oscillations during parabolic flight maneuvers that simulate Mars gravity, Moon gravity, and microgravity, in that order. While the ratio of and the correlation between GF and load force (LF) evolved progressively with practice in Mars gravity, these parameters stabilized much quicker to subsequently presented Moon and microgravity conditions. These data suggest that prior adaptation to one reduced-gravity field facilitates the CNS’s ability to update its internal model during exposure to other reduced gravity fields.